Application of augmented reality (AR) technology to locate the cutaneous perforator of anterolateral thigh perforator flap: A case report. Issue 1 (31st March 2021) - Nuri, Takashi; Mitsuno, Daisuke; Iwanaga, Hiroyuki; Otsuki, Yuki; Ueda, Koichi
Abstract: Multi‐detector row computed tomography (MDCT) makes it possible to visualize the peripheral perforators of the anterolateral thigh (ALT) flap. However, to transfer the preoperative MDCT angiography data to the operative field requires effective techniques. In this report, we describe an application of augmented reality (AR) technology to harvest the anterolateral thigh flap. A 36‐year‐old female presented with a T2N2 squamous cell carcinoma of the lateral tongue. The patient underwent hemiglossectomy and microsurgical reconstruction using the left ALT flap. Three dimensional (3D) images the vascular image, vascular with muscles and vascular with outline of the thigh ware prepared. Then these images were exposed to an AR device. The location of the perforator was determined using the 3D vascular image on AR. The intraoperative location of the cutaneous perforator corresponded with the predicted location which was confirmed using the AR technique. A 6 × 15 cm left ALT flap was transferred to the defect. Microsurgical anastomosis was performed on the left superior thyroid artery and the internal jugular vein. There were no complications during the postoperative course. At the 6‐month follow‐up, the patient showed no evidence of flap and donor site complications. Our experience suggests that AR technology may effectively support the transfer of MDCT angiography images onto surgical sites.